Prevalence of RHD alleles in Japanese individuals with weak D phenotype: Identification of 20 new RHD alleles. Issue 3 (17th May 2016) - Isa, K.; Sasaki, K.; Ogasawara, K.; Saito, M.; Tsuneyama, H.; Yabe, R.; Uchikawa, M.; Satake, M.
Abstract : We identified 46 different RHD alleles from 226 Japanese individuals with weak D phenotype, 26 of which had been previously described and 20 that were novel. Among these weak D individuals, the alleles with c.960G>A, c.845G>A ( RHD*15 ) or c.1013T>C ( RHD*01W.24 ) mutations were most prevalent with relative occurrences of 36·7%, 15·9% and 9·7%, respectively. These findings demonstrate that the prevalence of common weak D alleles in the Japanese population significantly differs from that of Caucasian populations.